Balloon expandable stent implantation for native and recurrent coarctation of the aorta—prospective computed tomography assessment of stent integrity, aneurysm formation and stenosis relief. Issue 15 (10th September 2009) - Chakrabarti, Santabhanu; Kenny, Damien; Morgan, Gareth; Curtis, Stephanie L; Hamilton, Mark C K; Wilde, Peter; Tometzki, Andrew J; Turner, Mark S; Martin, Robin P
Abstract : Background: Stenting for aortic coarctation is known to be effective in the medium term. Aneurysm formation following stent implantation is a recognised complication. However, data regarding aortic wall injury and stent integrity following stent placement are sparse. Objectives: We report comprehensive clinical, echocardiographic and prospective CT follow-up data following stenting for aortic coarctation from a single centre. Methods: Full data analysis of all patients undergoing balloon expandable stent implantation and follow-up procedures in a single tertiary congenital cardiac unit. Results: Between October 2002 and April 2008, we performed 102 coarctation stent procedures on 88 patients. Median age was 20.6 years (range 8.5–65) and median weight 65 kg (range 34–101). 94 stents (26 covered) were implanted. 12 procedures were re-dilatations. Stenting resulted in a reduction of the gradient across the site of coarctation, from a median of 20 mm Hg to 4 mm Hg. There were no procedure-related deaths. Four patients had immediate complications (one requiring emergency surgery). During median follow-up of 34.5 months (range 4.2–72.8), two patients had late complications requiring additional stent procedures. Follow-up CT data are available in 84 patients with MRI in one patient (96.5%). Only one patient developed a procedure-related aortic aneurysm. All stent fractures (n=7) occurred with a single stent design. Conclusions: Stenting for aortic coarctation and re-coarctation is effective with low immediate complication rates. CT is useful in the longer term for assessment of stent integrity and post-procedural aneurysm formation. Overall incidence of post-procedural aneurysm is rare and stent fractures were not seen with newer generation stents.